Diaphragm ultrasonography to estimate the work of breathing during non-invasive ventilation - Vivier, Emmanuel; Mekontso Dessap, Armand; Dimassi, Saoussen; Vargas, Frederic; Lyazidi, Aissam; Thille, Arnaud W.; Brochard, Laurent (Intensive care medicine, 2012)
Purpose Ultrasonography allows the direct observation of the diaphragm. Its thickness variation measured in the zone of apposition has been previously used to diagnose diaphragm paralysis. We assessed the feasibility and accuracy of this method to assess diaphragmatic function and its contribution to respiratory workload in critically ill patients under non-invasive ventilation. Methods This was a preliminary physiological study in the intensive care unit of a university hospital. Twelve patients requiring planned non-invasive ventilation after extubation were studied while spontaneously breathing and during non-invasive ventilation at three levels of pressure support (5, 10 and 15 cmH 2 O). Diaphragm thickness was measured in the zone of apposition during tidal ventilation and the thickening fraction (TF) was calculated as (thickness at inspiration − thickness at expiration)/thickness at expiration. Diaphragmatic pressure–time product per breath (PTP di ) was measured from oesophageal and gastric pressure recordings. Results PTP di and TF both decreased as the level of pressure support increased. A significant correlation was found between PTP di and TF (ρ = 0.74, p < 0.001). The overall reproducibility of TF assessment was good but the coefficient of repeatability reached 18 % for inter-observer reproducibility. Conclusions Ultrasonographic assessment of the diaphragm TF is a non-invasive method that may prove useful in evaluating diaphragmatic function and its contribution to respiratory workload in intensive care unit patients.